Testing for forecast rationality in financial markets the case of the Philippines - Bautista, Carlos (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1996)
The study examines a segment of the Philippine financial system within the efficient market framework. The period under study is broken down into three periods and tests for forecast rationality using a nonlinear least squares procedure were conducted. The main result of this study is not at all surprising. Philippine financial markets are in general efficient in conveying information except during the crisis period. The results may be explained by the fact that the crisis generated noise or normally present in non-crisis periods. This has a temporary effect of confusing market participants who are unable to distinguish market movements from the noise emanating from the uncertainties of the period and thus contaminating information sets. This leads to a rejection of the maintained hypothesis of rationality in the crisis period.